Impact of diet on cardiometabolic risk in patients with obstructive sleep apnea - Domenico Basta (Nutrimentum et Curae)
Obstructive sleep apnea (OSA) is a serious condition associated with increased morbidity and mortality from cardiovascular disease (CVD). It has been found that OSA and obesity commonly coexist. The American Academy of Sleep Medicine recommends diet-induced weight loss and exercise as lifestyle treatment options for OA. Epidemiological studies show that sleep apnea leads to increased risk factors for cardiovascular disease, including hypertension, obesity, and metabolic syndrome.